The emergence of novel coronavirus disease (COVID-19) in Bangladesh: Present status, challenges, and future management (Journal of Advanced Veterinary and Animal Research, 2020)
Immediate after the official declaration of COVID-19 in Bangladesh on 8 March 2020, it has created public panic which results in price plummeting of the capital market and price hike of many essential commodities. Worldwide, the outbreak of COVID-19 has declared a pandemic. In response, the Government of Bangladesh has initiated some strict measures such as stopping the entry of passengers from Europe, stopping on-arrival visas and self-quarantine for 2 weeks for all passengers return from abroad. Still, many loopholes exist at the entry points of Bangladesh. Most of the people of Bangladesh are yet to aware of the consequences of COVID-19. In this backdrop, this article has attempted to create public awareness about COVID-19, providing some guidelines to restrict this deadly disease, enlisting current challenges of this disease in Bangladesh. This review would be helpful to undertake future management practices against the fearsome COVID-19 in Bangladesh.Adv. Vet. Anim. Res., 7(2): 198-208, June 2020